The comprehensive expression analysis of circular RNAs in gastric cancer and its association with field cancerization. Issue 1 (December 2017) - Vidal, Amanda; Ribeiro-dos-Santos, André; Vinasco-Sandoval, Tatiana; Magalhães, Leandro; Pinto, Pablo; Anaissi, Ana; Demachki, Samia; Assumpção, Paulo; Santos, Sidney; Ribeiro-dos-Santos, Ândrea
Abstract Circular RNAs comprise a new class of long noncoding RNAs characterized by their 5′ and 3′ ends covalently joined. Previous studies have demonstrated that some circular RNAs act as microRNA sponges, and are associated with cellular proliferation in cancer. We were the first to analyze the global expression of circular RNAs in samples of patients without gastric cancer, gastric cancer, and matched tumor-adjacent gastric tissue. Among the samples, we identified 736 previously annotated circular RNAs by RNA-Seq. The tumor-adjacent tissue presented the higher abundance of circular RNAs and could not be considered as a normal tissue, reinforcing the notion of field effect in gastric cancer. We identified five differentially expressed circular RNAs that may be potential biomarkers of this type of cancer. We also predicted candidate microRNAs targets of the highest expressed circular RNAs in gastric tissues and found five miRNAs. Overall, our results support the hypothesis of circular RNAs representing a novel factor in the dynamic epigenetic network of gene regulation, which involves the microRNAs, its mRNAs targets, and the circular RNAs-derived genes. Further studies are needed to elucidate the roles and the functional relevance of the circular RNAs in human diseases.